Transition Risk in Climate Change: A Literature Review - Elisa Di Febo; Eliana Angelini (Risks)
Climate risk is the negative effect of climate change on several aspects of the environment, business, and society. There are two categories of climate risks: physical risks include direct impacts due to extreme events and chronic changes due to climate modifications that have become commonplace; the transition risk arises from the economic and regulatory adjustments required to shift toward reducing greenhouse gas emissions and the transition to renewable energy. The problem, in financial terms, is the correct assessment and quantification of transition risk, as it is not univocal in the literature. This research aims to provide a literature review on transition risk that permits filling this gap and identifying the proxies used for its representation and evaluation. Moreover, the analysis considers the critical aspect of the connection between transition and credit risk, as firms exposed to high transition risks may face challenges in maintaining creditworthiness. Results highlight the most commonly used proxies, including carbon pricing, CO2 or GHG emissions, and metrics from various databases. However, the findings emphasize the importance of integrating these indicators with broader factors, such as a company’s negative environmental impacts (e.g., waste production and water usage) and delays in technological adaptation from a forward-looking perspective.